Complex interventions in complex health systems: Hepatitis B birth-dose vaccination programs in the African region - Rakiep, Tasneem (Department of Public Health and Family Medicine, 2024)
Background: Of the 296 million chronic carriers of hepatitis B virus (HBV) infection worldwide, the majority are found in the African and Western Pacific regions. Neonates who acquire the infection from their mothers (mother-to-child transmission or MTCT) carry a 90% risk of chronicity. To prevent serious liver complications such as liver cancer, cirrhosis, and premature death, the World Health Organization (WHO) recommends hepatitis B vaccination at birth, followed by vaccination during infancy. Despite the longstanding implementation of universal hepatitis B infant vaccination programs, the African region maintains the highest prevalence (2.5%) of chronic HBV infection among children ≤5 years of age. While optimal coverage of the hepatitis B birth-dose vaccine could avert further infections in this region, weak implementation and poor program performance have raised global concern. This study provides a comprehensive update on the status of HBV MTCT in Africa and explores how complex interactions between intervention and the health system may influence the performance of hepatitis B birth-dose vaccination programs in the region. Methods: This qualitative systematic review study was conducted in two phases where phase 1 involved a scoping review and phase 2 the systematic review. The scoping review mapped current evidence on HBV MTCT and hepatitis B birth-dose vaccination programs in Africa. In addition, the scoping phase informed the development of an adapted systems-based logic model for assessing complexity in the design or causal pathway of hepatitis B birth-dose vaccination programs. For the qualitative systematic review, a Boolean search strategy was utilized to retrieve relevant peer-reviewed literature published between 2009–2022 indexed in PubMed, EBSCOhost databases, Scopus, and Web of Science, with supplementary searches conducted to identify any missed articles. No language restrictions were applied. Data extraction, synthesis and analysis were guided by the systems-based logic model tailored to systematic reviews of complex interventions. Results: Findings from the scoping review provided compelling evidence on the risk of HBV MTCT in Africa, spurred by the considerable burden of HIV co-infections in the region. Despite this, only 15 WHO African member states have so far adopted hepatitis B birth-dose vaccination programs, with noteworthy inconsistenciesin performance. Previous scoping reviews exploring the determinants of program success have been limited by the scanty representation of evidence from the African region. Furthermore, these reviews have failed to adequately address the complexities within the intervention or the multiple interactions across the intervention, the health systems and contexts which deliver them. Our systematic review search yielded 672 published records. Of these, 28 were judged to be eligible for inclusion. Among the 12 African states represented, the origin of evidence weighted highest in Nigeria (n=12) and Senegal (n=5). The performance of hepatitis B birth-dose vaccination programs across African states highlighted underlying complexities across multiple themes. The findings further emphasized the need for improved compliance with global recommendations when formulating national vaccine policies and guidelines; limitations of current vaccine supply chain systems; the need for renewed commitment towards intensified domestic investments complemented by donor support; ensuring capable and skilled cadres of health care workers, accurate and appropriate data collection and usage; expanded immunization services with outreach programs, and developments in maternal education and socio-economic status. Conclusion: We highlight the complex interactions between hepatitis B birth-dose vaccination programs and the health systems that deliver them. We further demonstrate how these complex interactions contribute to the sub-optimal performance of hepatitis B birth-dose vaccination programs in the African region. By identifying sources of complexity at the intersection of hepatitis B birth-dose vaccination programs and health systems in Africa, we can better inform the design of immunization programs responsive to the contexts they are embedded in. Ultimately, the performance of hepatitis B birth-dose vaccination programsin Africa extends beyond vaccine supply and is further driven by a multiplicity of program-specific, system-wide determinants that should be considered if the region is to progress towards improved control of HBV MTCT